Study of geometric effect to the crevice corrosion behaviour in stainless steel - Neena Kaylisia, Brum (2013)
This thesis deals with the geometric effect assessment to the crevice corrosion behaviour in stainless steel with a variations of crevice formers of different gap and depth dimensions. The objective of this thesis is to investigate the crevice corrosion behaviour of AISI 304 stainless steel in a variation of crevices geometry at room temperature. The thesis describes the effect of the geometric dimension on the crevice mouth to the AISI 304 stainless steel. This thesis also aimed to identify the crevice corrosion behaviour and to predict the fatigue life and identify the critical locations of the components. AISI 304 stainless steel were studied in this thesis which commonly used in industry. The crevice formers with variation dimension of gap and depth was machined in the laboratory. The method to analyse the corrosion rate and corrosion damage for the AISI 304 stainless steel is by weight loss. The observed weight loss data is then analysed by using corrosion rate equation accordance to American Society for Testing Material G1. From the results, it is observed that the amount of weight loss due to crevice corrosion behaviour increased as the crevice mouth opening increase where else at smaller crevice mouth opening. The result also can significantly shows the result of the differences between the general corrosion and the crevice corrosion; and also the corrosion behaviour inside the different in crevice gap and depth dimension